Taking a stab at modelling canine tooth biomechanics in mammalian carnivores with beam theory and finite-element analysis - Pollock, Tahlia I.; Panagiotopoulou, Olga; Hocking, David P.; Evans, Alistair R. (Royal Society open science, 2022)
Canine teeth are vital to carnivore feeding ecology, facilitating behaviours related to prey capture and consumption. Forms vary with specific feeding ecologies; however, the biomechanics that drive these relationships have not been comprehensively investigated. Using a combination of beam theory analysis (BTA) and finite-element analysis (FEA) we assessed how aspects of canine shape impact tooth stress, relating this to feeding ecology. The degree of tooth lateral compression influenced tolerance of multidirectional loads, whereby canines with more circular cross-sections experienced similar maximum stresses under pulling and shaking loads, while more ellipsoid canines experienced higher stresses under shaking loads. Robusticity impacted a tooth's ability to tolerate stress and appears to be related to prey materials. Robust canines experience lower stresses and are found in carnivores regularly encountering hard foods. Slender canines experience higher stresses and are associated with carnivores biting into muscle and flesh. Curvature did not correlate with tooth stress; however, it did impact bending during biting. Our simulations help identify scenarios where canine forms are likely to break and pinpoint areas where this breakage may occur. These patterns demonstrate how canine shape relates to tolerating the stresses experienced when killing and feeding, revealing some of the form–function relationships that underpin mammalian carnivore ecologies.